A147: Engaging Patients and Families in the Pediatric Rheumatology Care and Outcomes Improvement Network. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - DeWitt, Esi Morgan; Fricke, Kay; Bergheger, Lindsey; Griffin, Nancy; Laxer, Ronald M.; Jones, Karla B.; Gottlieb, Beth S.; Taylor, Janalee; Mims, Catherine C.; Robbins, Lisa M.; Lovell, Daniel J.; Noonan, Laura
Abstract : Background/Purpose: The Pediatric Rheumatology Care and Outcomes Improvement Network (PR‐COIN) is a multi‐site quality improvement learning network that aims to improve outcomes for children and adolescents with juvenile idiopathic arthritis. In addition to addressing variations in care practices, PR‐COIN has incorporated guidance and tangible contributions from patients and families to its national organizational and governance structure to drive improvement in JIA outcomes. PR‐COIN aims to grow this initiative to bring care providers, patients and family members together as co‐producers in improving care and outcomes. Methods: Various methods supporting family engagement are employed. PR‐COIN teams invite interested parents at their respective clinical sites to bring the parent perspective and priorities into local improvement work. To assure a reliable structure, a parent engagement specialist was employed to develop a platform for bringing families and care providers together. National conference calls facilitated by the specialist establish relationships across site representatives and begin goal setting for this group. Parents contribute to shared decision making project efforts. PR‐COIN's public website encourages family awareness and involvement in the network's improvement efforts. Results: 7 of 11 sites have welcomed parent contributions to their improvement efforts (e.g. focus groups, advisory activities, etc.). Parents and patients have participated in PR‐COIN's biannual conferences, sharing the family perspective and needs associated with JIA care. One parent brings a unique background and skillset as both a pediatrician with QI experience and the parent of a teen with JIA. This distinction prompted appointment to PR‐COIN's governing body. We incorporate patient perspectives into clinic process improvements (e.g. pain management, optimizing physical functioning), enhanced and refined PR‐COIN's Shared Decision Making tool, supporting stronger, more informed medication choice, and are developing best practices optimizing use of these materials in clinic. Finally our engaged parents are encouraging others to contribute ideas supportive of PR‐COIN structure, growth, strategy and improvement efforts. Conclusion: Parents and patients bring unique talents, insight and skills to the operation of quality improvement networks making efforts more relevant to the self‐identified needs of JIA families.